The role of hyaluronic acid, chitosan, and calcium sulfate and their combined effect on early bony consolidation in distraction osteogenesis of a canine model - Cho, BC; Park, JW; Baik, BS; Kwon, IC; Kim, IS (LIPPINCOTT WILLIAMS & WILKINS, 2002)
The purpose of this project was to study the effect of hyaluronic acid, calcium sulfate, and chitosan on early bony consolidation in distraction osteogenesis of a canine model. Sixteen dogs were used for this study. The lateral surface of the mandibular body was exposed in the subperiosteal plane, and the vertical osteotomy on the mandibular body was extended downward. An external distraction device was applied to the mandibular body, and the mandibular distraction was started 5 days after the operation at a rate of 1 mm/d up to a 10-mm distraction. The experimental group was then divided into a control group, chitosan group, hyaluronic acid group, calcium sulfate combined with hyaluronic acid group, and calcium sulfate combined with chitosan group, depending on the type of implantation material in the distracted area. After completing the distraction, implantation material was injected into the distracted area, although no material was implanted into the distracted area of the control group. After implanting the materials, the distraction device was left in place for 6 weeks to allow for bony consolidation. Four dogs were allocated to each group. Two dogs in each group (total of 8 dogs) were killed 3 weeks after implantation of the material, and the other 8 dogs were killed after 6 weeks. New bone was generated in the distracted zone of all groups. In the calcium sulfate combined with chitosan group and calcium sulfate combined with hyaluronic acid group, the formation of active woven bone was observed throughout the distracted zone. Moreover, the new bone seemed to be nearly normal cortical bone at 6 weeks after implantation. In the chitosan group and hyaluronic acid group, the development of new bone was observed in the distracted zone at 6 weeks. The amount was less than that in the calcium sulfate combined with hyaluronic acid group and calcium sulfate combined with chitosan group. These findings suggest that calcium sulfate and its combined materials seem to be quite effective in early bony consolidation in distraction osteogenesis.
Keywords: MORPHOGENETIC PROTEIN; FACIAL ASYMMETRY; HYDROXYAPATITE; GROWTH; REGENERATION; PLASTER; PARIS